Dynamics Of Legal Policy On Radicalization And Deradicalization Of Terrorism Prisoners - Tegar Aria Taba; Iman Santoso (Journal of Social Research, 2024)
The deradicalization program for terrorism prisoners is a crucial initiative in an effort to reduce the threat of terrorism in Indonesia. In this context, Law Number 22 of 2022 concerning the Prevention and Eradication of Terrorism is the legal basis that regulates various strategic aspects of this effort. This study aims to analyze the implementation and challenges in the deradicalization program of terrorism prisoners, focusing on the political aspects of law and its relevance in the international context. The research method used is a literature study to collect data and information related to the implementation of the deradicalization program, as well as policy analysis related to Law No. 22 of 2022. The results show that the deradicalization program of terrorism prisoners in Indonesia faces a number of challenges, including policy consistency, political consensus, and human rights protection. Nonetheless, successful international implementation offers views and best practices that can be applied to strengthen Indonesia's capacity to deal with the threat of terrorism. The conclusion of this study highlights the importance of multilateral cooperation, community-based inclusive approach, and human rights protection in the implementation of deradicalization programs. Based on these findings, it is recommended that the government strengthen international cooperation, improve related policies and regulations, improve education and training, and promote the values of moderation and tolerance as part of a sustainable strategy to address the threat of terrorism in Indonesia.